(untitled) (Global Journal of Human-Social Science, 2014)
Introduction-This paper will found its claims in a philosophy emerging from the systems of phenomenology, moving through monism, pluralism and finding its fundamental assertion in transcendental nondualism. Non-duality is commonly found in Buddhist and Indian epistemological and ontological studies, however I assert that it converges with classical western phenomenological philosophy in a manner that provides fruitful dialectical understandings related to the synthesis of conflicting opposites in instances of political impasse. The underlying assumption on which the integral assertion is founded is that many challenges facing the evolution of a more unified global civilization is based on a single under-considered dialectic of dualism and non-dualism. The failure to adequately understand the implications of these dialectical opposites limits solutions, and limits insights into the conditions of each. The challenges of absolutism within monism, the difficulties of relativism within pluralism can each be aided by non-dualism, while the challenge of subjective ideology in transcendent non-dualism is aided by grounding in the pragmatic conditions created by monism and pluralism. If we apply the approach of which I argue for, to problems in social contexts, a pattern of balancing of oppositional synthesis emerges. To demonstrate the approaches integration of ideology and pragmatism, I will first describe its philosophical basis and then apply the pattern to political conflicts to give support to the assertion that this method can be effectively applied, toward peace or further conflict, as desired.